1997
DOI: 10.1074/jbc.272.21.13467
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Autophosphorylated Calcium/Calmodulin-dependent Protein Kinase II to the Postsynaptic Density

Abstract: Calcium/calmodulin-dependent protein kinase II (CaMKII) undergoes calcium-dependent autophosphorylation, generating a calcium-independent form that may serve as a molecular substrate for memory. Here we show that calcium-independent CaMKII specifically binds to isolated postsynaptic densities (PSDs), leading to enhanced phosphorylation of many PSD proteins including the ␣-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid (AMPA)-type glutamate receptor. Furthermore, binding to PSDs changes CaMKII from a subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
240
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 280 publications
(253 citation statements)
references
References 48 publications
13
240
0
Order By: Relevance
“…Several studies have indicated that αCaMKII autophosphorylation of T286 enhances binding of the kinase to the PSD and several of its constituents (Bayer et al, 2001;Strack et al, 1997b;Strack and Colbran, 1998;Gardoni et al, 1999;Leonard et al, 2002;Strack et al, 2000). In addition, T286 phosphorylation has been shown to decrease the dissociation rate of the kinase from the PSD (Shen et al, 2000;Bayer et al, 2006;Yoshimura and Yamauchi, 1997;Dosemeci et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have indicated that αCaMKII autophosphorylation of T286 enhances binding of the kinase to the PSD and several of its constituents (Bayer et al, 2001;Strack et al, 1997b;Strack and Colbran, 1998;Gardoni et al, 1999;Leonard et al, 2002;Strack et al, 2000). In addition, T286 phosphorylation has been shown to decrease the dissociation rate of the kinase from the PSD (Shen et al, 2000;Bayer et al, 2006;Yoshimura and Yamauchi, 1997;Dosemeci et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Localization of CaMKII at the PSD has been proposed to be critical for its role in LTP (Lisman et al, 2002;Barria and Malinow, 2005). Furthermore, several different forms of neuronal activation, including treatments that lead to synaptic potentiation, have been shown to induce translocation of CaMKII to post-synaptic sites (Strack et al, 1997b;Shen and Meyer, 1999;Otmakhov et al, 2004;Dosemeci et al, 2001;Bayer et al, 2001). Accordingly, a more complete knowledge of the molecular mechanisms that regulate CaMKII binding to the PSD is likely to be crucial for our understanding of the biochemical events that occur during LTP.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…cross-sectional area, thickness and curvature, and the protein content of the PSD (e.g. Greenough et al 1978;Rutledge 1978;Rees et al 1985;Strevaag and Greenough 1985;Desmond and Levy 1986;Strack et al 1997;Hu et al 1998;Dosemeci et al 2001; except for the study of Sorra and Harris 1998). Time-lapse recording of the clusters of green fluorescence protein PSD95 in hippocampal neurons revealed rapid formation and remodeling of the PSD (Marrs et al 2001).…”
mentioning
confidence: 99%